Monolithic Poly(styrene-co-divinylbenzene) Columns for Supercritical Fluid Chromatography-Mass Spectrometry Analysis of Polypeptide - Zajickova, Zuzana; Nováková, Lucie; Svec, Frantisek (Analytical chemistry, 2020)
The organic polymer-based monolithic columns have been evaluated as the separation media for analysis of peptides using supercritical fluid chromatography-mass spectrometry (SFC-MS). We demonstrate for the first time the SFC-MS separation of a mixture of polypeptides carried out using poly(styrene-co-divinylbenzene) monolithic columns and carbon dioxide/methanol mobile phase. A gradient from 2 to 40% methanol modifier containing 0.1% TFA as an acidic additive was applied for the optimized elution and the separation was achieved in less than 3 min. Selected ion monitoring enabled detection of selected masses characteristic of three ionophoric pentadecapeptide antibiotics gramicidin A, B, and C and their two corresponding isoforms. Furthermore, their identity was confirmed through determination of their [M + 2H]2+, [M + 2Na]2+, and [M + H + Na]2+ ions acquired by positive-ion electrospray ionization-mass spectrometry (ESI-MS).
Keywords: methanol; teplota; poréznost; vysokoúčinná kapalinová chromatografie; Methanol; gramicidin; Carbon Dioxide; Biosensing Techniques; Porosity; superkritická fluidní chromatografie; hmotnostní spektrometrie s elektrosprejovou ionizací; Temperature; Chromatography, High Pressure Liquid; molekulová hmotnost; Protein Isoforms; polystyreny; oxid uhličitý; Polystyrenes; biosenzitivní techniky; Chromatography, Supercritical Fluid; Gramicidin; protein - isoformy; Molecular Weight; Spectrometry, Mass, Electrospray Ionization